Coupled Random Fixed Point Theorems for Mixed Monotone Nonlinear Operators - Kongban, Chayut; Kumam, Poom; Martínez-Moreno, Juan (Communications in Mathematics and Applications, 2019)
In this paper, we prove the existence of a random coupled coincidence and coupled random fixed point theorems in complete separable metric space without the mixed \(g\)-monotone property. The results are used to prove existence of random solutions for random integral equation.